2017
DOI: 10.1021/acs.jproteome.6b01062
|View full text |Cite
|
Sign up to set email alerts
|

Blood Metabolic Signatures of Body Mass Index: A Targeted Metabolomics Study in the EPIC Cohort

Abstract: Metabolomics is now widely used to characterize metabolic phenotypes associated with lifestyle risk factors such as obesity. The objective of the present study was to explore the associations of body mass index (BMI) with 145 metabolites measured in blood samples in the European Prospective Investigation into Cancer and Nutrition (EPIC) study. Metabolites were measured in blood from 392 men from the Oxford (UK) cohort (EPIC-Oxford) and in 327 control subjects who were part of a nested case-control study on hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
66
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 45 publications
12
66
3
Order By: Relevance
“…Diet, fitness level, alcohol intake and body mass index might be modifiable determinants of these metabolites. [22][23][24][25][26] The current results on phosphatidylcholines and sphingomyelins (treelet component 1) and risk are broadly consistent with those of other prospective studies investigating individual metabolites, including our previously published results, 6 which were conducted in a subset (~35%) of the current study population. For example, we previously reported inverse associations of many individual phosphatidylcholines, all of which were included with positive loadings in treelet component 1 or 3, with risk of advanced stage prostate cancer, and some associations remained when restricting the analysis to aggressive prostate cancer.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Diet, fitness level, alcohol intake and body mass index might be modifiable determinants of these metabolites. [22][23][24][25][26] The current results on phosphatidylcholines and sphingomyelins (treelet component 1) and risk are broadly consistent with those of other prospective studies investigating individual metabolites, including our previously published results, 6 which were conducted in a subset (~35%) of the current study population. For example, we previously reported inverse associations of many individual phosphatidylcholines, all of which were included with positive loadings in treelet component 1 or 3, with risk of advanced stage prostate cancer, and some associations remained when restricting the analysis to aggressive prostate cancer.…”
Section: Discussionsupporting
confidence: 88%
“…In line with our results, treelet transform applied to untargeted metabolomics and lipidomics data from EPIC‐Potsdam also identified a pattern characterized by positive loadings on a sphingomyelin, three phosphatidylcholines and other glycerophospholipids (a class including phosphatidylcholines). Diet, fitness level, alcohol intake and body mass index might be modifiable determinants of these metabolites …”
Section: Discussionmentioning
confidence: 99%
“…Numerous metabolites were associated with BMI and WC. These metabolites included many previously associated with BMI and other measures of adiposity, including urate, the BCAAs and other amino acids, several acyl‐carnitines, and glycerophospholipids . Several novel associations were also found, including for specific sphingolipids, nucleotides, modified FAs (hydroxylated or carboxylated), and bile acids.…”
Section: Discussionmentioning
confidence: 89%
“…Many studies have used metabolomic profiling to identify metabolites and metabolic pathways that are altered in individuals with overweight and obesity. These include several smaller studies (10 to 140 participants) that compared metabolite levels in groups of adults defined by body size measures (7)(8)(9)(10)(11)(12)(13)(14), as well as studies with larger sample sizes derived from a specific population (15) or prospective cohort studies (16)(17)(18)(19)(20)(21)(22)(23)(24). Collectively, these studies have found that levels of several amino acids, including the branched chain amino acids (BCAAs) leucine, isoleucine, and valine, are higher in obesity, whereas other amino acids are lower (8,9,11,(13)(14)(15)(16)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, higher concentrations of acylcarnitines and branched‐chain aminoacids have been associated with an increased risk of CVD. Specific metabolomic signatures, mainly based on lipid species and amino acids, have also been related to obesity and T2D …”
Section: Introductionmentioning
confidence: 99%